Search for Galactic PeV gamma rays with the IceCube Neutrino Observatory - Aartsen, M; Abbasi, R; Abdou, Y; Ackermann, M; Adams, J; Aguilar, J; Ahlers, M; Altmann, D; Andeen, K; Auffenberg, J; Bai, X; Baker, M; et al. (American Physical Society, 2013)
Gamma-ray induced air showers are notable for their lack of muons, compared to hadronic showers. Hence, air shower arrays with large underground muon detectors can select a sample greatly enriched in photon showers by rejecting showers containing muons. IceCube is sensitive to muons with energies above ∼500 GeV at the surface, which provides an efficient veto system for hadronic air showers with energies above 1 PeV. One year of data from the 40-string IceCube configuration was used to perform a search for point sources and a Galactic diffuse signal. No sources were found, resulting in a 90% C.L. upper limit on the ratio of gamma rays to cosmic rays of 1.2×10 -3 for the flux coming from the Galactic plane region (-80 â‰2lâ‰2-30; -10 â‰2bâ‰25) in the energy range 1.2-6.0 PeV. In the same energy range, point source fluxes with E-2 spectra have been excluded at a level of (E/TeV)2dΦ/ dE∼10-12-10-11 cm-1 s-1 TeV -1 depending on source declination. The complete IceCube detector will have a better sensitivity (due to the larger detector size), improved reconstruction, and vetoing techniques. Preliminary data from the nearly final IceCube detector configuration have been used to estimate the 5-yr sensitivity of the full detector. It is found to be more than an order of magnitude better, allowing the search for PeV extensions of known TeV gamma-ray emitters. © 2013 American Physical Society.